Literature Review Of The Role Of Digital Training In Improving The Success Of MSMEs - Widhi Wicaksono; Suyatin Suyatin; Nugroho Wicaksono (Pasundan Social Science Development, 2026)
This study aims to analyze the role of digital training in increasing the success of MSMEs and identify factors that influence the effectiveness of digital training for MSME actors based on a systematic literature review..This research uses a descriptive exploratory approach using an approach to literature review or library study, namely referring to various literature, such as books, dissertations, scientific journals and the internet.The literature review shows that digital training plays a crucial role in improving the competency, strategic mindset, and success of MSMEs through the use of digital technology, social media, and e-commerce. Furthermore, the study also shows that the effectiveness of digital training is influenced by several factors, including community and instructor support, the entrepreneur's education level, the use of digital platforms, and the duration and sustainability of the training program. These factors contribute to improving MSMEs' digital skills and their ability to develop their businesses in the digital era.